Alex Cross's Trial - Patterson, James (Grand Central Pub., 2010)
Detective Alex Cross tells the story of an ancestor, Abraham Cross, and his experiences with lawyer Ben Corbett, recounting one man's pursuit of justice in the face of the resurgence of Ku Klux Klan racism and violence in 1906 Eudora, Mississippi.